2021
DOI: 10.3390/cells10102566
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B1 Accumulation’s Effects on Autosomal Dominant Leukodystrophy (ADLD): Induction of Reactivity in the Astrocytes

Abstract: Autosomal dominant leukodystrophy (ADLD) is an extremely rare and fatal neurodegenerative disease due to the overexpression of the nuclear lamina component Lamin B1. Many aspects of the pathology still remain unrevealed. This work highlights the effect of Lamin B1 accumulation on different cellular functions in an ADLD astrocytic in vitro model. Lamin B1 overexpression induces alterations in cell survival signaling pathways with GSK3β inactivation, but not the upregulation of β-catenin targets, therefore resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A link between lamin B1 overexpression and signalling pathway alterations has been recently supported by our last article, reporting that lamin B increase leads to inactivation of glycogen synthase kinase (GSK)3β, but not the upregulation of β-catenin targets and to a reduction of astrocyte survival in vitro [ 52 ]. Interestingly, astrocytes overexpressing lamin B1 show increased immunoreactivity for both GFAP and vimentin together with NF-κB phosphorylation and c-Fos increase, suggesting astrocytes reactivity and substantial cellular activation [ 52 ].…”
Section: Lamin B-related Laminopathiesmentioning
confidence: 97%
“…A link between lamin B1 overexpression and signalling pathway alterations has been recently supported by our last article, reporting that lamin B increase leads to inactivation of glycogen synthase kinase (GSK)3β, but not the upregulation of β-catenin targets and to a reduction of astrocyte survival in vitro [ 52 ]. Interestingly, astrocytes overexpressing lamin B1 show increased immunoreactivity for both GFAP and vimentin together with NF-κB phosphorylation and c-Fos increase, suggesting astrocytes reactivity and substantial cellular activation [ 52 ].…”
Section: Lamin B-related Laminopathiesmentioning
confidence: 97%
“…Although on the gene level a therapy has been suggested ( Giorgio et al, 2019 ), the mechanisms behind ADLD remain unknown. Recent studies have contributed to the elucidation of the underlying disease mechanisms for targeted therapy toward specific cellular populations and biochemical pathways ( Ratti et al, 2021a , b ). The focus of these studies were astrocytes overexpressing lamin B1, for which it was shown that they contained several nuclear alterations absent from oligodendrocytes overexpressing lamin B1.…”
Section: Lamin B1 In the Aging Brainmentioning
confidence: 99%